Cancers related to exposure to arsenic at a copper smelter. Issue 1 (January 1995) - Enterline, P E; Day, R; Marsh, G M
Abstract : OBJECTIVE–This is an update of an earlier study on the relation between exposure to arsenic in air and deaths from respiratory cancer. The purpose was to verify earlier findings of a supralinear dose response relation and to examine relations with other cancers, particularly those reported in studies on drinking water. METHODS–An earlier study of 2802 men who worked at a copper smelter for a year or more during the period 1940-64 and who were followed up for deaths during the period 1941-76 was updated until 1986. Estimates of exposure for the period 1977-1984 were added. RESULTS AND CONCLUSIONS–The additional follow up confirms the earlier finding that at low doses the increments in death rates for respiratory cancer for a given increment in dose are greater than at high doses. The additional follow up also shows significant increases in cancer of the large intestine and bone, and SMRs > 150 for cancer of the buccal cavity and pharynx, rectal cancer, and kidney cancer. There was a positive relation between exposure to arsenic in air and kidney and bone cancer, but none for the other cancers, except respiratory.